Persistent cytosolic Ca2+ increase induced by angiotensin II at nanomolar concentrations in acutely dissociated subfornical organ (SFO) neurons of rats - Izumisawa, Yu; Tanaka-Yamamoto, Keiko; Ciriello, John; Kitamura, Naoki; Shibuya, Izumi (ELSEVIER, 2019)
It is known that angiotensin II (AII) is sensed by subfornical organ (SFO) to induce drinking behaviors and autonomic changes. All at picomolar concentrations have been shown to induce Ca2+ oscillations and increase in the amplitude and frequency of spontaneous Ca2+ oscillations in SFO neurons. The present study was conducted to examine effects of nanomolar concentrations of All using the Fura-2 Ca2+-imaging technique in acutely dissociated SFO neurons. All at nanomolar concentrations induced an initial [Ca2+](i) peak followed by a persistent [Ca2+](i) increase lasting for longer than 1 hour. By contrast, [Ca2+](i) responses to 50 mM K+, maximally effective concentrations of glutamate, carbachol, and vasopressin, and All given at picomolar concentrations returned to the basal level within 20 min. The All-induced [Ca2+](i) increase was blocked by the AT1 antagonist losartan. However, losartan had no effect when added during the persistent phase. The persistent phase was suppressed by extracellular Ca2 + removal, significantly inhibited by blockers of L and P/Q type Ca2+ channels, but unaffected by inhibition of Ca2+ store Ca2+ ATPase. The persistent phase was reversibly suppressed by GABA and inhibited by CaMK and PKC inhibitors. These results suggest that the persistent [Ca2+](i) increase evoked by nanomolar concentrations of All is initiated by All receptor activation and maintained by Ca2+ entry mechanisms in part through L and P/Q type Ca2+ channels, and that CaMK and PKC are involved in this process. The persistent [Ca2+](i) increase induced by All at high pathophysiological levels may have a significant role in altering SFO neuronal functions.
Keywords: RECEPTOR SIGNALING PATHWAYS; CIRCUMVENTRICULAR ORGANS; INTRINSIC EXCITABILITY; SENSITIVE NEURONS; INHIBITORY INPUTS; CALCIUM-CHANNELS; MEDIAN-EMINENCE; CENTRAL ROLES; NUCLEUS; PLASMA